Peran Pemangku Kepentingan Dalam Pembentukan Komunitas Guna Mencapai Ketahanan Sosial Ekonomi Masyarakat - Irine Kusumatantya (Jurnal Wilayah dan Lingkungan, 2013)
Climate change has become one of the global issues which affect various aspects of life, such as a rise in sea levels that results in flood and tidal flood. Adaptation measures need to be done in order to overcome the susceptibilities. It will be more efficient and effective if the adaptation measures are conducted communally through community development. However, the limited access and resources make people difficult to adapt. Therefore, the intervention of other stakeholders is needed in order to create access and to mobilize society in the community development. Unlike developed countries, society participation in developing countries still needs to be mobilized through the intervention of some stakeholders. Every stakeholder has different task, function, and responsibility so that they can complete each other. The stakeholders which are involved in community development come from three sectors, that are government, non-governmental institutions, and society in the community itself. In doing their role, the stakeholders may not work properly. The role dysfunction will have negative effects on the sustainability of the formed community. One of the examples is the establishment of housing saving group in Panjang Baru district, Pekalongan. In its process, the role dysfunction occurs. It results in the stagnant community development which weakens socio-economic resilience of the society built through the development of that housing saving group.